The genome sequence of the minke whale, Balaenoptera acutorostrata Lacépède, 1804 [version 1; peer review: 2 approved] - Nicholas J. Davison; Andrew Brownlow; Phillip A. Morin (Wellcome Open Research)
We present a genome assembly from an individual female Balaenoptera acutorostrata (the minke whale; Chordata; Mammalia; Artiodactyla; Balaenopteridae). The genome sequence has a total length of 2,772.90 megabases. Most of the assembly is scaffolded into 22 chromosomal pseudomolecules, including the X sex chromosome. The mitochondrial genome has also been assembled and is 16.42 kilobases in length.